Estudio de caso de la resolución quirúrgica de un proceso exostósico en miembro posterior izquierdo, en la articulación interfalángica próximal en un equino deportivo - Alarcón Urgilés, Diego Germán (2018)
Bone exostosis is a degenerative pathology involved in locomotion problems. This articular pathology is common and frequent in sport horses and its occurrence can be observed in front and posterior limbs. The proximal interphalangeal joints; conformed by the first phalange or proximal phalange and the secondary phalange, shows more frequency of appearance. Its possible to control the affection with a palliative approach, nevertheless the affection has a degenerative origin making it not curable and limiting the animal in a locomotor aspect. Surgery in these cases will depend on the type of lesions and which joint is compromised; the procedure tries to ensure evolution in the animal locomotion and the reintegration of the animal normal activity. The following study describes the arthrodesis of the proximal interphalangeal joint on the posterior limb of an 8 year old male sport horse, castrated, called “INTI”, who presented a 3/5 claudication of the left posterior limb. The radiological and clinical study concluded that the animal needed surgical corrective treatment. The surgery looks in achieving a mechanical ankyloses through joint fixation with orthopaedic material. The technique used to correct the case was applying three cannulated screws, 5.5x 0.3, through the proximal interphalangeal joint on the posterior limb. The surgical procedure was successful. The joint fixation and technique used were adequate, obtaining a correct patient recovery. After 8 months, the animal dint showed any trace of claudication on his left posterior limb, fully recovered he restored his normal activity and competed in 2017. It is possible to conclude that the surgical technique applied to correct the pathology has high recovery rates and prevents economical loses and animals with high potential, allowing owners and horse riders to avoid premature loses of young animals who suffer from this condition.